Uncontained [videorecording (DVD)] - Nelson, Morley; Nelson, Morley; O'Meara, P. (Peter); LeBlanc, Hayley (Cineverse, 2025)
A mysterious drifter struggles to protect an abandoned boy and his little sister from an infection that turns people into a feral-like state and a ruthless militia leader searching for his missing daughter.